Analisis Kebutuhan Guru Matematika Dan Siswa Madrasah Tsanawiyah Dalam Penggunaan Modul Matematika Terintegrasi - Susanti, Nawal Ika; Insaniyah, Anyes Lathifatul; Aulia, Rikha Warda; Kusuma, Via Arik (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
This research aims to determine the extent to which teachers and students in the field need integrated mathematics modules in the Madrasah Science Competition and the effectiveness of using these modules. This research is quantitative research. Data analysis used used N-Gain to test the effectiveness of the integrated mathematics module. The results of this research show that 82.39% of students stated that they really needed this integrated mathematics module due to the lack of references related to integrated mathematics, especially questions in Arabic. The results of the analysis of the needs of mathematics teachers from 6 madrasahs were 100% and also stated that integrated mathematics modules were really needed in guiding students preparing for the Madrasah Science Competition. The integrated mathematics module developed by researchers also has a high effectiveness value of 0.7675 so that the module can be disseminated to madrasas and the community.